A Study on the Distribution of Different Types of Intermittent Exotropia Among Patients with Intermittent Exotropia - Anubhuti Srivastava; Ranjana Shukla; Salal Khan (Galore International Journal of Health Sciences and Research, 2026)
Background: Intermittent exotropia is a type of strabismus or eye misalignment, where one eye occasionally turns outward, away from the nose. Unlike constant exotropia, which is always present, intermittent exotropia happens periodically. The affected eye may drift outward intermittently while the other eye remains straight Aim: To determine the type occurrence, incidence, clinical characteristics and angle of deviation (near and distance) of intermittent exotropia: divergence excess, basic exotropia or convergence insufficiency among 100 patients of age group 3-20 years. Material and Methods: It was a retrospective cross-sectional study. A total of 100 patients with age of 3-20 years with intermittent exotropia had included in the study. Demographic and clinical data were collected of all the patients presenting to OPD of the SEH (Sitapur Eye Hospital) from 2020-2024. The subjects were the patients of the department of ophthalmology of Sitapur Eye Hospital. The Procedure was to collect demographic data and clinical data then identify the type of intermittent exotropia (divergence excess, basic exotropia and convergence insufficiency), occurrence, incidence , clinical characteristics and to observe angle of deviation of different types by clinical data and patients who has difference in their angle of deviation every month which we had determined by follow up of those patients and measure their angle of deviation by the prism bar cover test at 20 feet and at 33 cm without and with a +3.00 D add at near and the patients wore their correction, if any, and a small light source served for fixation in both distance and near vision, one eye of the patient was then occluded for 30-45 minutes and the procedure repeated. Results: Among the 100 patients with intermittent exotropia, 55% were females and 45% were males. Intermittent exotropia was more common in the younger age group (3-12 years) compared to 13-20 years. Divergence excess was the most prevalent subtype, accounting for 70% of cases, followed by basic exotropia (20%) and convergence insufficiency (10%). The mean angle of deviation was approximately 20 prism diopters (PD) at near and 15 PD at distance. Patients with divergence excess demonstrated greater deviation at distance fixation, whereas convergence insufficiency showed larger deviations at near fixation. The angle of deviation varied with visual stress and fatigue, reflecting the intermittent nature of the condition. Conclusion: The Intermittent Exotropia is very common problems in the females and young children. Hence early intervention with vision therapy can significantly improve eye alignment and visual function in patients with intermittent exotropia. These findings underscore the importance of early diagnosis and targeted treatment. Keywords: Intermittent Exotropia, Misalignment, Paediatric Optometry, Divergence Excess, Convergence Insufficiency